Testing personal orientations - organizational climate fit using polynomial regressions, response surface, and bootstrapping - Lee, Allison Gim Wah; Nora Muda,; Abdul Rahman Othman, (Penerbit Universiti Kebangsaan Malaysia, 2019)
Personal orientations-organizational climate fit as a predictor of organizational commitment was examined using a sample of 350 Malaysian medical doctors from public and private hospitals in the northern states of Malaysia. The fit hypothesis was tested using polynomial regression and response surface methodology, followed by bootstrapping to estimate confidence intervals and for significance testing of response surface features. The results generally indicated that the personal orientations-organizational climate fit has a positive impact on the affective and normative organizational commitment of doctors. The need for achievement and the need for power were found to be significant dimensions that predicted the affective-normative commitment.